2021
DOI: 10.1002/jcph.1823
|View full text |Cite
|
Sign up to set email alerts
|

Precision Dosing for Tacrolimus Using Genotypes and Clinical Factors in Kidney Transplant Recipients of European Ancestry

Abstract: Genetic variation in the CYP3A4 and CYP3A5 (CYP3A4/5) genes, which encode the key enzymes in tacrolimus metabolism, is associated with tacrolimus clearance and dose requirements. Tacrolimus has a narrow therapeutic index with high intra‐ and intersubject variability, in part because of genetic variation. High tacrolimus clearance and low trough concentration are associated with a greater risk for rejection, whereas high troughs are associated with calcineurin‐induced toxicity. The objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The landmark, NIH-funded, multicenter DEKAF study provides significant information regarding CYP3A5 genotypes and IR tac dosing requirements. This was an observational study in 1969 patients, which determined that *1/*1 and *1/*3 expressors had a 305 and 181% increase in oral IR tac clearance compared with *3/*3 individuals [11]. In additional DEKAF work, Sanghavi et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The landmark, NIH-funded, multicenter DEKAF study provides significant information regarding CYP3A5 genotypes and IR tac dosing requirements. This was an observational study in 1969 patients, which determined that *1/*1 and *1/*3 expressors had a 305 and 181% increase in oral IR tac clearance compared with *3/*3 individuals [11]. In additional DEKAF work, Sanghavi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high PK variability profile, tac is universally monitored using whole blood trough concentrations [7][8][9][10][11]. As an orally administered medication, tac is absorbed through the gut and is metabolized via CYP3A4/5 that catalyze its conversion to various inactive O-demethylated metabolites [11,12]. Tac is also a substrate for P-glycoprotein, which is involved in the efflux of multiple drugs [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between GCs and tacrolimus are more seen in patients carrying the CYP3A5*1 allele[ 133 ]. GCs significantly contribute to inter-individual variability of apparent clearance of oral tacrolimus[ 134 ]. On the other hand, some studies reported that cyclosporine decreases prednisolone clearance by 25%-30% in kidney transplant patients[ 135 ], while others found no difference in dose-adjusted exposure of prednisolone when co-administered with cyclosporine or tacrolimus[ 136 ].…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…Interactions between GCs and tacrolimus are more seen in patients carrying CYP3A5*1 allele [133] . GCs significantly contributes to inter-individual variability of apparent clearance of oral tacrolimus [134] . On the other hand, some studies reported that cyclosporine decreases prednisolone clearance by 25-30% in kidney transplant patients [135] , while others found no difference in dose-adjusted exposure of prednisolone when co-administered with cyclosporine or tacrolimus [136] .…”
Section: Drug-drug Interactionsmentioning
confidence: 99%